Analisis Komparatif Persepsi Konsumen Terhadap Smartphone Realme dan Oppo di Bangkinang Kota - T. Junilda Fera Paningsih; Librina Tria Putri; Henrizal Henrizal (LP2M Universitas Ibrahimy, 2023)
The development of Smartphone technology has been quite quick from the time it was initially published until now, with various Smartphone brands circulating in the market. This study aims to determine differences in consumer perceptions of promotions, features, prices and designs of the Realme 6 Pro and Oppo A92 smartphones. The sampling technique used was quota sampling using a questionnaire. The number of samples is as many as 100 samples. The analysis technique used is the validity test, reliability test, and manova test. The results of this study indicate that the promotional activities, features, prices and designs of the two smartphones have significant differences in consumer perceptions.